Central nervous system nocardiosis in Queensland: A report of 20 cases and review of the literature. Issue 46 (November 2016) - Rafiei, Nastaran; Peri, Anna Maria; Righi, Elda; Harris, Patrick; Paterson, David L.
Abstract : Abstract: Nocardia infection of the central nervous system (CNS) is an uncommon but clinically important disease, often occurring in immunocompromised individuals and carrying a high mortality rate. We present 20 cases of microbiologically proven CNS nocardiosis diagnosed in Queensland from 1997 to 2015 and review the literature from 1997 to 2016. Over 50% of cases occurred in immunocompromised individuals, with corticosteroid use posing a particularly significant risk factor. Nine (45%) patients were immunocompetent and 3 had no comorbidities at time of diagnosis. Nocardia farcinica was the most frequently isolated species (8/20) and resistance to trimethoprim–sulfamethoxazole (TMP-SMX) was found in 2 isolates. Overall, 35% of our patients died within 1 year, with the majority of deaths occurring in the first month following diagnosis. Interestingly, of the 7 deaths occurring at 1 year, 6 were attributed to N farcinica with the seventh isolate being unspeciated, suggesting the virulence of the N farcinica strain.